STRATEGI BRANDING POLITIK DI ERA MEDIA SOSIAL TWITTER: ANALISIS KEBERHASILAN BRANDING JOKOWI-MA’ARUF AMIN PADA PILPRES 2019 - RIDO ASHABUL KAHFI; TITIN PURWANGISIH (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to analyze the political branding strategy used by the Jokowi-Ma'ruf Amin winning team in the 2019 Presidential Election, especially through the Twitter platform. Amid various religious issues and criticisms of the Jokowi regime's performance, Jokowi-Ma'ruf's electability had decreased. Therefore, the winning team must design an appropriate communication strategy to restore the positive image of the candidate pair. This study uses a qualitative descriptive approach with the help of NVivo 12 Plus software to analyze content from Twitter. The focus of the analysis includes political brand equity indicators, namely brand association, brand loyalty, and brand awareness. The results of the study show that Jokowi-Ma'ruf Amin's political branding strategy is more dominated by brand association and brand loyalty, which reached 42.67% and 36.67%, respectively. Brand association plays an important role in building Jokowi-Ma'ruf's personal branding through the support of political parties such as PDI-P and PKB, while brand loyalty can be seen from the strong support of modernist and traditional Islamic groups such as Nahdlatul Ulama (NU). On the other hand, brand awareness does not contribute significantly to branding strategy, with only 19.33% of the total analysis results. This study highlights the importance of managing brand association and brand loyalty in forming an effective political image on social media